Implementation and effectiveness of continuous kangaroo mother care: a participatory action research protocol - Marzieh Mohammadi; Anne-Marie Bergh; Mohammad Heidarzadeh; Mahammadbagher Hosseini; Niloufar Sattarzadeh Jahdi; Leila Valizadeh; Behzad Sarvaran; Sevil Hakimi (BMC, 2021)
Abstract Background The efficacy of continuous kangaroo mother care (C-KMC) in reducing neonatal mortality and morbidity among low birthweight and premature infants has been confirmed. Despite the recommendations of the World Health Organization, UNICEF, and the Ministry of Health of Iran to use C-KMC for eligible hospitalized neonates, this type of care is not performed due to implementation problems. This protocol aims to describe the design, implementation, and assessment of C-KMC in one tertiary hospital by means of participatory action research. Methods The objective of this study is to design and implement a C-KMC program for neonates that will be performed in two phases using a stages-of-change model. The first phase will be conducted in three consecutive activities of designing, implementing, and assessing the introduction of C-KMC. The second phase of the study has a before-and-after design to assess the effectiveness of C-KMC by comparing the length of preterm neonates' stay in hospital and exclusive breastfeeding at discharge before and after implementing C-KMC. Discussion KMC is an important component of neonatal developmental care as part of family-centered care. Applying this type of care requires creating appropriate strategies, budget allocation, and clear and coordinated planning at different levels of the health system. The stages-of-change model is one of the appropriate approaches to the implementation of C-KMC.